HUMANS AND NATURE: THE MEANING OF COMMUNICATION IN THE NGAJI RASA RITUAL OF THE DAYAK SEGANDU TRIBE IN INDRAMAYU - ,, Khaerunnisa; Septadinusastra, Vina Alvinia; Wulan Sari, Ratu Arti (E-Journal of Cultural Studies; Vol 18 No 1 (2025): Volume 18 Number 1 February 2025DO - 10.24843/cs.2025.v18.i01.p05, 2025)
The Dayak Hindu Buddhist Community of Bumi Segandu Indramayu is a group of people who belong to a community that has a particular faith. This community performs three rituals, namely Ngaji Rasa, Kumkum and Mepe. The purpose of this research is to find out how messages are conveyed in the rituals of the Indramayu Dayak tribe and what message meaning is conveyed from the ritual activities of Ngaji Rasa, Kumkum, and Mepe. This research uses qualitative methods with ethnographic communication studies, with data collection techniques through observation, interviews and documentation. The results of the research conducted that (1) communicating messages in the Ngaji Rasa, Kumkum, and Mepe rituals is not conveyed directly, but important messages are communicated both verbally through advice, and nonverbally through ritual attributes. (2) The meaning of the message to be conveyed from the Ngaji Rasa, Kumkum, and Mepe ritual activities is to show the close relationship between humans and nature, where nature is considered a source of life for the Indramayu Dayak people who must be respected and maintained. Keywords : Ritual Communication, Dayak Segandu Tribe, Ethnography, Message Meaning